Compatibility of pentoxifylline and parenteral medications. Issue 4 (23rd December 2019) - Campbell, Anna L; Petrovski, Michael; Senarathna, SMDK Ganga; Mukadam, Nabeelah; Strunk, Tobias; Batty, Kevin T
Abstract : Objective: To investigate the physical and chemical compatibility of pentoxifylline (PTX) with a range of parenteral medications used in neonatal intensive care. Design: PTX and drug solutions were combined in glass vials, inspected for physical incompatibility and evaluated on the basis of PTX concentrations for chemical compatibility. Results: No precipitation, colour change or turbidity was observed in any of the test mixtures. The PTX concentration was approximately 5.5% lower when combined with undiluted calcium gluconate injection (100 mg/mL). The PTX concentration ratios for all other combinations, including diluted calcium gluconate injection (50 mg/mL), were in the range of 99.5%–102%. Conclusion: In simulated Y-site conditions, PTX was found to be compatible with 15 parenteral medications and six total parenteral nutrition solutions. Based on PTX concentration tests, it would be prudent to avoid mixing PTX with undiluted calcium gluconate injection.